Scientific Data in the Holy Quran: A Study on Major Verses and Themes - Luckman Muthuvallur (Penerbit Hellow Pustaka, 2024)
Science is the result of relentless experiments of humankind through a gradual process. Science may abrogate its conclusions of today based on findings of new experiments. If science finds anything, it is the work of different ages with efforts of many people. Quran is the revelation of all wise Allah who created universe. It’s not surprising that Quran contains knowledge about universe and its functions. Modern Islamic preachers adopted science as best way for the propagation of Islam and an easy tool for attracting the modern minds. They compared the Quran with modern science and produced many books to deliver the compatibility of the holy Quran with modern science. It is evident that scientific interpretation of the holy Quran helps many people to understand Quran and convert to Islam. Many scientists studied scientific data in Quran and embraced Islam. Regrettably, majority of them left Islam due to the errors occurred during the interpretation of the Quran using scientific evidences. Even if that does not make any error to the holy Quran helped in understanding the need of carefulness in the interpretation of the Quran. Majority of criticisms against Quran coming out of erroneous interpretation without proper knowledge or qualification.